Enhancement of thiodicarb efficacy using synergists and role of carboxylesterase in potentiation of synergistic activity in brinjal fruit and shoot borer (Leucinodes orbonalis Guenee) - Pasayat, B; Tripathy, M K (Plant Science Today, 2025)
The primary cause of low productivity in brinjal is the infestation by the fruit and shoot borer and field control failure is due to the evolution of insecticide resistance. In the current study, an investigation has been carried out in bimonthly intervals from Nov-2021 to Sept-2022 to assess the efficacy of some selected synergists with a carbamate, thiodicarb and the role of carboxylesterase enzyme in imparting insecticide resistance in Brinjal fruit and shoot borer from two locations of Odisha, Bhubaneswar and Bargarh. Out of all the synergists tested in the topical bioassay method, propargyl-oxy-phthalimide (PP) being a member of esterase hydrolase inhibitor group provided remarkable SR ratio (10.78) during May- 2022 in the Bhubaneswar population while that of Bargarh population indicated comparatively higher value (12.68) indicating efficacy of the synergist lowering the dose of thiodicarb to 1.464 µg/µl compared to 18.564 µg/µl when thiodicarb alone is used. This can be related to enhanced levels of detoxifying enzyme, Carboxylesterase in Bhubaneswar during May 2022 (4.52-fold) and Bargarh (5.36-fold) population compared to laboratory-reared susceptible population revealing the role of carboxylesterase enzyme in detoxification mechanism behind the efficacy of the synergists. This study highlights the importance of synergists like PP and Triphenyl phosphate (TPP) and suggests their inclusion in the existing pest management strategies of L. orbonalis in a wider agricultural area they reduce doses of insecticides and hence reduce impact on the environment which can lead to sustainable agriculture.